Association Between Peripapillary Bruch's Membrane Shape and Intracranial Pressure: Effect of Image Acquisition Pattern and Image Analysis Method, a Preliminary Study - Malhotra, Kiran; Patel, Megh D.; Shirazi, Zainab; Moss, Heather E. (Frontiers in Neurology, 2018)
Background/Aims: High intracranial pressure (ICP) is associated with changes in peripapillary Bruch's membrane (pBM) shape on optical coherence tomography (OCT) images of the optic nerve head. It is not known if image acquisition pattern and analysis method impact this association. Materials and Methods: Cross sectional OCT scans of the optic nerve head were obtained at six angles using a radial scan pattern in 21 subjects immediately prior to ICP measurement via lumbar puncture. On each image, Bruch's membrane was manually segmented and defined by either 14 or 16 semi-landmarks and either rater identified, or distance identified boundaries. For each of these four image analysis strategies, geometric morphometric analysis identified the first principal component of Bruch's membrane shape for all images and for the set of images taken at each angle. Repeated measures ANOVA of the first principal component magnitude (PC1) for all images assessed for shape difference between image angles. Linear generalized estimating equation models assessed association between angle specific first principal component magnitudes (PC1) and ICP for each angle. Receiver operating characteristic analysis assessed angle specific PC1s' ability to differentiate elevated from normal ICP. Results: The first principal component represented deflection into the vitreous for all scan angles, but quantitatively differed across scan angles (p < 0.005, repeated measures ANOVA). Angle specific first principal components were positively correlated with ICP (p < 0.005 for all angles, generalized estimating equation models). All angle specific first principal components showed excellent ability to classify ICP (area under curve ≥ 0.8 for all). These results were independent from image analysis strategy. Discussion: Though qualitative changes in Bruch's membrane shape are similar regardless of cross-sectional angle of the 2-D OCT scan, they differ quantitatively between OCT scan angles, meaning that pBM is not axially symmetric and therefore PC1 extracted from different 2-D scan angles can't be compared between individuals. However, we do not identify an optimal scan angle for classification of ICP since there is a similarly strong linear relationship between the first principal component of shape and ICP and angle specific first principal components of Bruch's membrane shape showed similarly excellent ability to differentiate elevated from normal ICP. The results support development of Bruch's membrane shape extracted from 2-D cross sectional optic nerve head OCT scans as a biomarker of ICP and emphasize the importance of consistency of scan angle. This is relevant for developing diagnostic protocols that use OCT to detect high ICP states.